The importance of sleep for athletic performance - Marshall, G. J. G.; Turner, A. N. (Strength and Conditioning Journal, 2016)
Ensuring that athletes function optimally throughout training is an important focus for the strength and conditioning coach. Sleep is an influential factor that affects the quality of training, given its implications on the recovery process. Intense training may predispose athletes to risk factors surrounding disturbed sleep patterns. These may be due to inherent physical exertion, commitment to extensive training schedules, the effects of travel, domestic or international, and the pressures that competition evokes. Educating athletes on the implications of sleep should be implemented by strength and conditioning coaches to optimize athlete recovery, promote consistent sleep routines, and sleep length.